Countering Subtractive Bilingualism with Additive Bilingualism in the Albanian Language - Diedon DORAMBARI (Prizren Social Science Journal, 2021)
The English language is the lingua franca of education, trade, and employment.  However, with such a global influence, the English language sometimes interferes with the native languages via subtractive bilingualism.  The aim of this essay is to explain the negative effects of subtractive bilingualism on a global scale in general, elaborate on its negative effects on the Albanian language in particular, and propose solutions to the problem.